2002
DOI: 10.1073/pnas.232244199
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine control of a sexually dimorphic behavior by a few neurons of the pars intercerebralis in Drosophila

Abstract: In Drosophila, locomotor activity is sexually dimorphic and the brain area controlling this dimorphism has been mapped. The neurons of the pars intercerebralis (PI) have been suggested to participate in such differences between males and females. However, the precise physical nature of the dimorphism, the identity of the PI neurons involved, and the nature of the neuronal signal coding the dimorphism remain unknown. In this study, we used a video-tracking paradigm to characterize further the pattern of locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 37 publications
(41 reference statements)
6
91
2
Order By: Relevance
“…On the other hand, in insects, JH is expressed in both sexes [34] and differentially affects male and female behavior [38], morphology [39], development and locomotion [38], but the novelty of our results is that the effect of JH upon immune response seems to be sex dependent at least in the monarch butterfly. In females two out of three immune parameters were affected by the JH while in males only PO was affected.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, in insects, JH is expressed in both sexes [34] and differentially affects male and female behavior [38], morphology [39], development and locomotion [38], but the novelty of our results is that the effect of JH upon immune response seems to be sex dependent at least in the monarch butterfly. In females two out of three immune parameters were affected by the JH while in males only PO was affected.…”
Section: Discussionmentioning
confidence: 60%
“…In Drosophila, insulin signalling has been implicated in ethanol sensitivity (Corl et al, 2005), sexually dimorphic locomotor activity (Belgacem and Martin, 2002;Belgacem and Martin, 2006) and age-related locomotor impairment (Jones et al, 2009), and in a Drosophila model of -amyloid-induced neurotoxicity (Chiang et al, 2010). Here, we report that inhibition but not activation of insulin signalling in mushroom body neurons throughout larval development disrupts starvation-induced food intake and growth of foraging third instar larvae.…”
Section: Discussionmentioning
confidence: 78%
“…It has served as a model to study the function of insulin signalling in a variety of processes (e.g. Broughton et al, 2005;Belgacem and Martin, 2002;Belgacem and Martin, 2006;Corl et al, 2005) (reviewed by Teleman, 2010). Increased levels of insulin suppress starvation-dependent feeding behaviour (Wu et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously suggested that TO could act as a juvenile hormone (JH) carrier protein based on its protein sequence similarity with JH binding proteins (JHBPs) (Lerro and Prestwich, 1990). Moreover, we have previously found that JH level is involved in sexual dimorphism of locomotor activity (Belgacem and Martin, 2002). to 1 flies lack such sexual dimorphism and this could be rescued both genetically, by expressing to under the timeless (tim) driver, and pharmacologically, using methoprene, a JH analog.…”
Section: Introductionmentioning
confidence: 99%